A further case of a new syndrome including midface retraction, hypertrichosis, and skeletal anomalies. Issue 6 (December 1979) - Donnai, D; Harris, R
Abstract : The clinical and radiological features of a male child with multiple malformations are described. He appears to be an example of a new syndrome recently described by Schinzel and Giedion (1978).